Promoting better integration of health information systems: best practices and challenges - Michelsen, Kai (WHO Regional Office for Europe, 2015)
This report addresses the current trends in Member States of the European Union (EU) and European Free Trade Association (EFTA) on how to promote better integration of health information systems (HISs). To understand what better integration means from a pragmatic perspective, we conducted interviews with experts from 13 EU Member States, the results of which were combined with the findings from a literature search. The results from the interviews stress the need (i) for ongoing work on some “basics”, such as data availability and quality, inventories of data and registries, standardization, legislation, physical infrastructure and workforce capacities; (ii) to continue with the work on more “concept-driven” indicator sets; (iii) to define what better integration means and to demonstrate concrete benefits of integration; (iv) to build leadership for capacity building in further integration of HISs; and (v) for a further international exchange about ongoing activities in this area.
Health Evidence Network (HEN) synthesis report, ISSN 2227-4316
Keywords: lékařská praxe založená na důkazech; zdravotnické informační systémy; Health Information Systems; telemedicína; sběr dat; Data Collection; lékařská informatika; Telemedicine; Evidence-Based Practice; kooperační chování; veřejné zdravotnictví; Cooperative Behavior